Analisis Kesulitan Pembelajaran Mahārah Al-Qirā’ah pada Siswa Kelas VII Program Khusus MTs Negeri 6 Klaten - Nur Syarifah Hidayati; Agung Setiyawan (Mahira: Journal of Arabic Studies & Teaching, 2023)
This study aims to determine the difficulties experienced by students in learning mahārah al-Qirā'ah, the factors that cause students' difficulties in learning mahārah al-Qirā'ah, and efforts to overcome students' difficulties in learning mahārah al-Qirā'ah. This research is a qualitative research with the type of case study research. The subjects of this study were 10 students of class VII special program, Arabic teacher and homeroom teacher of class VII special program. While the data collection in this study through observation, interviews, and documentation. Data analysis was carried out using descriptive qualitative analysis through data condensation techniques, data presentation, and drawing conclusions. Meanwhile, the data validity technique uses triangulation techniques, namely technical triangulation and source triangulation. The results of this study indicate that the difficulties experienced by students in learning mahārah al-Qirā'ah are difficulties in reading Arabic texts, difficulties in mastering Arabic vocabulary, and difficulties in translating Arabic texts. The factors that cause students to have difficulty learning mahārah al-Qirā'ah include 1) internal factors, namely the low interest and motivation in student learning, student learning attitudes that are not orderly and disciplined, and the background of students coming from public elementary schools. And 2) external factors, namely the lack of support from the family, the teacher's learning method is not right, the community environment is not supportive, the learning media is not appropriate, the learning curriculum is not right, and the lack of allocation of learning time.